Faktor Risiko Kejadian Preeklampsia Berat/Eklampsia pada Ibu Hamil - Sutiati Bardja (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
Preeclampsia is a disease caused by pregnancy and causes of maternal death. The purpose of this study is to determine the risk factors associated with the incidence of preeclampsia in pregnant women in Arjawinangun Regional Hospital in 2019. The population of maternity women in the VK room of Arjawinangun Hospital in the August 2019 to January 2020 period. Selecting the sample purposively namely pregnant women in the VK Room so that 156 respondents consisted of 39 respondents who experienced severe preeclampsia/eclampsia as a case sample and 117 respondents who did not experience severe preeclampsia/eclampsia as a control sample. Data analysis techniques using univariate analysis, bivariate analysis, and multivariate analysis. The results showed that there was a relationship between age (p = 0,000), parity (p = 0.003), education (p = 0,000), history of preeclampsia (p = 0,000), family history (p = 0,000), weight gain (p = 0,000) ), the number of fetuses (p = 0.0061) and calcium consumption (p = 0,000) have a significant risk, while the economy (p = 0.640), passive smoking (p = 0.681) and occupation (p = 0.469) have no significant relationship with the incidence of severe preeclampsia/eclampsia in pregnant women in Arjawinangun District Hospital in 2019. The results of multivariate analysis showed the most dominant factor in the incidence of preeclampsia was age with Exp (B) or OR 12.5.